Analysis of MUC4 expression in the prostatic adenocarcinoma and its pathological implications - Sundaram, Sandhya; C., Simon Durai Raj; R., Krishnakumar; D., Santhosh; Narashiman, Sangeetha; D., Prathiba (International Journal of Research in Medical Sciences, 2016)
Background: Expression of various types of mucins has been documented in several malignancies and seems to play a sentinel role in some epithelial malignancies. MUC1 and MUC4 are two transmembrane mucins that are involved in cell signalling events that drive the proliferation of cells. Therefore, mucins may be important biomarkers for early diagnosis and targeted therapy due to their frequently altered expression pattern in carcinomas. The objective of the study was to determine the expression pattern of MUC-4 in prostate cancer and to correlate the expression with clinicopathological parameters. Methods: Thirty cases of prostate carcinomas of different grades were selected from the case files of our institute for the study. Immunohistochemistry was done on all cases using monoclonal antibodies against MUC- 4 by the avidin biotin technique. The expression and pattern of staining were analyzed .Staining pattern in the adjacent benign areas were also noted. Results: Our study showed that expression of MUC4 was considerably down regulated in prostate cancer tissues when compared to normal or benign prostatic tissue. Few cases of prostate cancer showed a moderate staining while majority cases of adjacent normal areas were moderate to strongly positivity. Conclusions: The results of our study implies that MUC4 is down regulated in prostate cancer and this may be of significance for diagnostic application and tumor progression in prostate cancer. Since MUC4 is known to modulate HER2/ErbB2 signalling it may prospectively prove to be useful in prostate cancer therapy.